Evaluasi Tempat Uji Kompetensi Teknisi Otomotif dalam Peningkatan Mutu Lulusan Sekolah Menengah Kejuruan - Sartono Manto Suwarno; Bambang Ismanto (Kelola: Jurnal Manajemen Pendidikan, 2020)
The objective of this research is to evaluate the context, input, process and product components in Evaluating Implementation of Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga. The implementation of this research is conducted with a descriptive evaluative research method using CIPP (context, input, process and product) evaluation model. Data collection in this research is carried out through interviews, observations and documentations which are validated through Focus Group Discussion (FGD) activities. The results of this research stated that: 1). Context Evaluation of Implementation Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga is based on the identification of needs and policies by the government; 2). Input Evaluation of Implementation Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga already has technical and administrative readiness in the Field of Automotive Engineering Expertise; and Competency Test for Automotive Technicians; 3). Process Evaluation of Implementation Competency Test Place for Automotive Technician is still not in accordance with expectations and plans that have been made; 4). Product Evaluation of Implementation Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga has been carried out, however there are still many obstacles encountered in it. The conclusion of this research is the decision on the Implementation Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga is more incremental. It seems to be an important consideration that the Implementation Competency Test Place for Automotive Technician at SMK Negeri 2 Salatiga should be continued with some improvements.